Digital-Based Cash Waqf Management at Waqf Institutions in Indonesia - Lubis, Haniah; Nuryanti, Nuryanti; Adibtia, Eggi Zulfahri (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2024)
The objective of this study is to analyze the implementation of digital-based cash waqf management in six waqf institutions in Indonesia, and explore the impact of digitalization on transparency, accountability, and public participation while addressing the challenges and strategies related to regulations, infrastructure, and digital literacy. A qualitative research approach was employed, with case studies in six waqf institutions implementing digital systems. Data were gathered through relevant documentation and academic publications. This study employs a comparative methode to analyze digital-based cash waqf management across six waqf institutions in Indonesia. The comparison involves identifying similarities, differences, and successes, presented in tabular form to facilitate the analysis of management practices. The findings reveal that while digitalization enhances transparency, accountability, and public participation, significant challenges persist. Key challenges include non-adaptive regulations, uneven technological infrastructure, and low public digital literacy. Strategies to address these obstacles include capacity-building, supportive regulatory development, and increased public education on digital cash waqf.